Connectivity and trade relativity: The case of ASEAN - Venus Lun; Jan Hoffmann (Journal of Shipping and Trade (JST), 2016)
To explore the concept of connectivity and trade relativity (CTR), this paper presents a research model to illustrate: (1) the impact of shipping connectivity on two types of trade flows, and (2) the mediating effect of intra-regional trade ("intra-trade") on the relationship between shipping connectivity and extra-regional trade ("extra-trade"). Understanding the relationships among shipping connectivity and the two types of trade flows (intra-trade and extra-trade) provides insights for managers to make their location decision and identify countries with appropriate levels of shipping connectivity to conduct their trading related activities, and for policy makers to develop measures to enhance trade competitiveness and shipping connectivity. This study also contributes to the concepts of trade creation and trade diversion through the examination of shipping connectivity. A regional trade agreement such as the Association of Southeast Asian Nations (ASEAN) leads to more intra-trade. Some of this trade is new (trade creation) and some might substitute for extra-trade (trade diversion). By incorporating shipping connectivity into the analysis, we show that the trade diversion effect will be reduced thanks to the overall increased shipping connectivity, as the latter will not only benefit intra-trade but also extra-trade.
Keywords: 650; International Trade; Member Country; Regional Integration; Trade Flow; Free Trade Agreement